A fully digital physical unclonable function based temperature sensor for secure remote sensing - Cao, Yuan (2020)
Turnkey solutions that combine energy-efficient remote sensing and secure communication of telemetry are desirable in data collection, risk control and situation appraisal with the large scale deployment of resource constrained Internet of Things devices. In this paper, a new low-cost physical unclonable function (PUF) based temperature sensor for secure remote temperature sensing is proposed. The design exploits the approximately linear positive temperature coefficient of CMOS inverter in super-threshold operation to calibrate the running frequency of ring oscillator (RO) in a reconfigurable RO PUF at different temperature. The RO frequency corresponding to the sensed temperature is fed into a randomizer seeded by the input challenge to select new RO pairs for comparison to generate a random, unique and physically unclonable digital tag, which is valid for a selected input challenge to a target device at a particular temperature. Using only standard logic cells and a very simple structure, the proposed temperature sensor can be easily implemented on FPGA and integrated into other digital systems. It protects the integrity of the sensed information by preventing falsified sensor data and masquerade sensing node. The FPGA implementation of our proposed design has demonstrated the feasibility of making a trust temperature telemetry system out of PUF.